KEPADATAN POPULASI BAKTERI PELARUT FOSFAT PADA LAHAN GAMBUT TERDEGRADASI AKIBAT TERBAKAR - Sari, Tati Lola; Ekyastuti, Wiwiek; Ekamawanti, Hanna Artuti (JURNAL HUTAN LESTARI, 2018)
Phosphate in the soil is a nutrient that plays an important role in the process of plant growth. In nature, the availability of phosphate is aided by phosphate solubilizing bacteria (PSB) which are common in the rhizosphere. The purpose of this study is to obtain the information on density of PSB population density isolated from former burnt peatlands in Kuala Dua village with different depth and distance from the trench edges. Peat soil sampling was taken by using systematic sampling method and bacterial isolation was carried out on Pikovhskaya media using pour plate method, while the calculation of bacterial density was counted by plate method. The results showed that the lowest BPF colony population density on burnt peat soil was 9.17 x 104 CFU/g soil (isolated from peat depth of 20-50 cm) and the highest colony density of PSB was 141,000 x 104 CFU/g of soil (isolated from peat depth of 0-20 cm). The existence of PSB on burnt peatlands is a biological potential that could be developed to support the efforts of restoring the degraded peatlands.Keywords: burnt peatlands, phosphate solubilizing bacteria, restoration